2016
DOI: 10.1177/1039856216629841
|View full text |Cite
|
Sign up to set email alerts
|

Rate of community treatment orders and readmission orders following reconfiguration of community mental health services

Abstract: Rates of CTOs and readmissions varied across services and further research is warranted to identify factors associated with these increased rates. Additionally, the very high rate of CTOs in the catchment areas warrants further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…Nationally, 60 % of recalls ended in revocation during 2014/15 [16]; our rate of 68 % was slightly higher. There is a paucity of international studies of recall and revocation, but one small study from Victoria, Australia report a 62 % revocation level [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Nationally, 60 % of recalls ended in revocation during 2014/15 [16]; our rate of 68 % was slightly higher. There is a paucity of international studies of recall and revocation, but one small study from Victoria, Australia report a 62 % revocation level [25]. …”
Section: Discussionmentioning
confidence: 99%
“…There is, therefore, the paradoxical possibility of restricting a patient’s autonomy via a CTO with the therapeutic purpose of nurturing their autonomy. The effectiveness of CTOs in facilitating recovery has also been extensively reported on and some report that there is insufficient evidence for believing they are any better at improving quality of life than voluntary care (1013).…”
mentioning
confidence: 99%
“…Some rates are based on total populations, others on adults only and some are based on adults up to the age of 65. 3,14…”
Section: Discussionmentioning
confidence: 99%
“…Some rates are based on total populations, others on adults only and some are based on adults up to the age of 65. 3,14 Patients were middle aged (30-50 years) with a slight male predominance (56.4%). 4,6,17 The percentage of all involuntary in-patients who received an out-patient commitment order at discharge varied between 9.2 and 11.9% over the study years, which is about the same level as reported from England, 14 but lower than other jurisdictions.…”
Section: Use Of Out-patient Commitmentmentioning
confidence: 99%
See 1 more Smart Citation